Screening for Chronic Kidney Disease (CKD) in a high risk population using a Point of Care Instrument for creatinine measurement: A community based study (The Bellville South Africa Study) - Krige, Tammy (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMedSc)--Stellenbosch University, 2017